Digital Religion: Social Media and the Spread of Salafi Thought in Indonesia - Alam, Lukis; Nurwahidin, Nurwahidin; Katni, Katni; Suyurno, Salahudin (FIKRAH, 2025)
This study examines religious phenomena that occur on social media platforms, especially YouTube, Twitter (X), Facebook, Instagram, and Telegram. The platform is a medium for spreading understanding of Salafi thought in Indonesia using a digital ethnographic approach. This article aims to understand the pattern of dissemination, interpretation, and acceptance of Salafi ideas in Indonesian society. The focus of the study includes aspects of content visibility, audience engagement, and ideological models that are raised. Data was obtained from the accounts of Indonesian Salafi figures who have a large following and reach a wide audience. This article focuses on audience engagement indicators such as user interaction, content dissemination and participatory responses analyzed with the theory of religious mediatization and digital religious authority. This study reveals how preachers adjust their da'wah strategies to increase the visibility and legitimacy of religious authority in the online space. This article contributes to the understanding of the relationship between religion and technology and the real impact of digital media on the formation of religious authority and participation in the context of Indonesian Islam.